2019
DOI: 10.4081/aiua.2019.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Malignant solitary fibrous tumor of urinary bladder: A rare clinical entity

Abstract: Solitary Fibrous Tumors (SFTs) are mesenchymal tumors occurring in several sites. Urinary bladder SFTs are quite rare. Eighteen cases are described in the literature and only two of them had malignant features. SFTs comprise a histologic spectrum of mesenchymal neoplasms that show fibroblastic differentiation. The signs and symptoms are non specific. Immunohistochemistry plays a pivotal role in the diagnosis, differentiating SFTs from other spindle cell mesenchymal tumors. Malignant criteria are considered the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Age at presentation varies between fourth and sixth decades of life with slightly high predominance in men. Approximately 18 cases have been reported occurring in the bladder with only 2 cases among females [2 , 3] . The first 5 cases of SFTs in mediastinum and pleura were reported in 1931 by Klemperer.…”
Section: Discussionmentioning
confidence: 99%
“…Age at presentation varies between fourth and sixth decades of life with slightly high predominance in men. Approximately 18 cases have been reported occurring in the bladder with only 2 cases among females [2 , 3] . The first 5 cases of SFTs in mediastinum and pleura were reported in 1931 by Klemperer.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies showed that pelvic [27,30,41], abdominal [27,42], and pleural [27,40,43] SFTs tend to be larger than tumors appearing in other locations, and extrapleural SFTs may show potentially malignant behavior [44], especially those with limb localization [45]. Generally, over the years, SFTs have been described in various localizations, including the liver [46,47], kidney [48][49][50], pancreas [23,51,52], sigmoid colon [31], mesocolon [14], omentum [53,54], urinary bladder [55], caecum wall [56], mesorectum [41], prostate [57], spermatic cord [58], testis [59], scrotum [60], female gynecological tract, especially the vulva [61,62], vagina [63], breast [64][65][66], heart and pericardium [33,67,68], epicardium [69], pulmonary artery [70], trachea [71], larynx [32,72], tongue [15], salivary glands [73]<...…”
Section: Anatomical Locationmentioning
confidence: 99%
“…Interestingly, FNA (fine needle aspiration), together with nuclear STAT6 immunoreactivity, has been reported to be an additional tool in the diagnosis of SFTs [117]. However, a core needle biopsy or an open incisional biopsy [118] and an immunohistochemical analysis are needed to confirm the diagnosis [55]. In STS, an open incisional biopsy may comprise treatment due to tumor dissemination, and as such could only be indicated in singular cases, e.g., in unfeasibility of a core needle biopsy [119].…”
Section: Diagnosismentioning
confidence: 99%
“…Taken together, as mediators of endocytosis and related to cell signaling, caveolins are implicated in both carcinogenesis and tumoral suppression [ 189 ], and they probably act as promoters in the case of malignant bladder tumors [ 62 , 190 ]. However, and despite the potential interest that proteins found in the serosa may have, the tumoral lesions arising in this bladder layer are exceedingly rare [ 191 , 192 ]; thus, the influence of this molecular environment in BC is largely unknown [ 193 , 194 , 195 ].…”
Section: Insights Into the Histopathology Of Bladder Cancer By Proteomicsmentioning
confidence: 99%